Role of Cytosorb in Severe Covid 19 Patients to Combat Cytokine Storm – A Case Series of 3 Patients (Global Journal of Medical Research, 2022)
PURPOSE To demonstrate the effect of Cytosorb on reducing the cytokine levels seen due to cytokine storm in severe COVID 19 patients MATERIAL METHODS COVID 19 patients with severe HRCT scoring and on NIV MV were included in the study The time points considered in our study are D0 D 1 D 3 D 5 to look for the levels of inflammatory markers post therapy along with the outcome of patients on D 7 in terms of mortality or off NIV MV RESULTS Statistical significance tested for the reduction in the WHO score value resulted p value of 0 85 The mean baseline value of the inflammatory markers CRP D-DIMER IL 6 were 66 94 780 67 144 67 respectively with range 56 5-81 331- 1211 124-167 respectively p values 0 60 0 95 0 18 respectively 7- day outcome of the study was 100 mortality CONCLUSION The results of our study are in favor of no additional benefits of CYTOSORB therapy in improving the clinical outcome among COVID 19 patients However the 7-day outcome of our study reported 100 mortality to confirm the complete ineffectiveness of the therapy a study on large group population is encouraged
Keywords: COVID-19 disease; cytosorb therapy; 9-point ordinary scale developed by WHO